Comparative utilization of two sources of expellerextruded soybean meal as a replacement for on-farm processed soybean in diets of growing-finishing pigs - Adesehinwa A. O. K (African Journal of Pig Farming, 2013)
Thirty pigs averaging 30 ± 1.1 kg were randomly assigned by origin and weight to one of three dietary treatments in a randomized complete block to determine the comparative utilization of two sources of expeller-extruded soybean meal as a replacement for on-farm processed soybean in diets of growing-finishing pigs. The result revealed that pigs fed diets containing the expelled soybean meal (ESM) had decreased (P<0.05) average daily gain (ADG) compared to pigs fed the on-farm processed soybean resulting in between 13-17% reduction in the ADG. The expelled soybean meal samples resulted in comparable (P>0.05) gains even though slight numerical differences were observed. Feed efficiency was 18 to 24% significantly (P<0.05) poorer for pigs fed the expelled soybean meal diets compared to the improvement observed in the feed conversion of pigs when fed the on-farm processed soybean. Conclusively, the gains as well as the efficiency of feed utilization obtained with the on-farm processed soybean were significantly (P<0.05) superior compared to the expeller- extruded soybean but the serum metabolites of the pigs were observed to be unaffected by the different processing methods.